The Role Of Theoretical And Practical Research In The Development Of Computer Linguistics - Khusanboyeva, Mukhlisa (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2025)
Computational linguistics is a component of applied linguistics, which uses the achievements of theoretical linguistics. Computational linguistics and theoretical linguistics complement each other. Today, one of the important needs is to raise the status of the Uzbek language and bring it to the ranks of authoritative languages. Computational linguistics is one of the convenient opportunities created to fulfill this need. This article is aimed at covering the above-mentioned topic.